Innovation in accounting tasks: empirical study in two professional groups - Machado, Maria João Cardoso Vieira; Vicente, Célia Cristina da Silva; Laureano, Raul Manuel da Silva (Business: Theory and Practice, 2016)
The aim of this study is to contribute to the knowledge on innovation in accounting tasks, from the point of view of two professional groups. Its goals are: evaluating the importance given by the professionals to accounting tasks; identifying whether there is convergence between the two professional groups, regarding the importance of the tasks; examining whether there is an association between the professionals’ individual characteristics and the importance they attach to the tasks. Two professional groups were surveyed: 105 financial officers of the top 500 Portuguese companies; and 412 Chartered Accountants. The results obtained allowed us to conclude that the respondents attach more importance to the traditional tasks, linked to the concept of a monetary-oriented accountant, and less importance to the more innovative tasks, related to business strategy; there is no convergence between the two professional groups in terms of the importance of the accountants’ participation in the strategic tasks. Regarding the association between individual characteristics and the level of importance assigned to the accounting tasks, we found an influence of the following characteristics: gender; academic degree of the professionals; and the institution where that degree was obtained.